One-pot synthesis and characterizations of (SrFe₁₂O1₁₉)ᵪ - (Ni₀.₅ZN₀.₅Fe₂O₄)₁ˍᵪ nanocomposite ferrites - Abdullah Ahmad, Hartini (2017)
Nanocomposite ferrites are known as an exchange - spring magnet when they are well exchange coupled. This phenomena has been studied by synthesized (SrFe12O19) - (Ni0.5Zn0.5Fe2O4) nanoparticles using a one-pot thermal treatment method. This technique is a single reaction mixture involving metal nitrates and the capping agent which is polyvinyl pyrrolidone (PVP). Nanocomposite ferrite nanoparticles were succeed to synthesize via single reaction technique. The starting materials used were PVP as the capping agent, deionized water and metal nitrates as the precursors. This study was divided into 3 sections. For the first part, we investigated the effect of PVP as a capping agent. Composite ferrites with 20% of hard and 80% of soft ferrites were fabricated by varying the concentrations of PVP (0 to 0.06 g/ml). For the second part, we studied the influence of phase distributions on the particles. Nanocomposite ferrites of (SrFe12O19)x – (Ni0.5Zn0.5Fe2O4)1-x were synthesized by varying the contents of x (0.1 to 0.9). The last part of this research was on calcination temperatures. Samples of (SrFe12O19)x – (Ni0.5Zn0.5Fe2O4)1-x where (x = 0.8 and 0.9) were calcined at 600 ºC to 1000 ºC for 3 hours. Several characterizations were carried out such as X-ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM), Fourier Transform Infra-red (FT-IR), Thermogravimetric Analysis (TGA), microstructure analysis using Field Emission Scanning Electron Microscope (FESEM) and Transmission Electron Microscope (TEM). From the XRD analysis, both soft and hard phases were coexist for every samples. The optimum concentration of PVP was 0.06 g/ml which gave a better magnetic properties compared to other concentrations of PVP used. In addition, (SrFe12O19)x – (Ni0.5Zn0.5Fe2O4)1-x nanocomposite with x = 0.9 shows highest Hc value with 5692 G and the optimum calcination temperature was found out to be at 800 ºC. From the analyses show that the hard/soft nanocomposite ferrites were able to synthesize by this one-pot thermal treatment method. Therefore, this technique is one of the promising method to fabricate nanocomposite permanent magnet.